2018
DOI: 10.1111/dmcn.13996
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental difficulties in children with idiopathic clubfoot

Abstract: A substantial minority of children with idiopathic clubfoot show neurodevelopmental difficulties. Children with idiopathic clubfoot might present additional difficulties in motor skills, perception, and language. Children with idiopathic clubfoot and marked neurodevelopmental symptoms show poorer parent-reported clubfoot treatment satisfaction. Neurodevelopmental difficulties should be considered in clinical practice of idiopathic clubfoot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(85 reference statements)
1
11
0
Order By: Relevance
“…Sex and clubfoot laterality did not affect HRQoL. However, the coexistence of NDD appearing in IC above chance significantly decreased HRQoL. The observation that 41% of the children with IC reported pain or discomfort is alarming and indicates that the general treatment goal of a pain‐free foot is not being achieved in a large proportion of the affected children.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Sex and clubfoot laterality did not affect HRQoL. However, the coexistence of NDD appearing in IC above chance significantly decreased HRQoL. The observation that 41% of the children with IC reported pain or discomfort is alarming and indicates that the general treatment goal of a pain‐free foot is not being achieved in a large proportion of the affected children.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, the 90th percentile for any domain score has been defined as a cut‐off for potential clinical concerns . The Five to Fifteen questionnaire has demonstrated acceptable to excellent interrater and retest reliability and has previously been used to screen for NDD in children with IC . It was used in this study to classify children with IC into those with and without NDD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Lööf et al . is the first which shows these differences and is predicated on their prior work which revealed that motor skills in children with idiopathic clubfoot were affected by factors other than musculoskeletal deficiencies.…”
mentioning
confidence: 99%